Variability in flowering behaviour and physico-chemical traits of bael (Aegle marmelos) cultivars under subtropical conditions - D PANDEY; S K SHUKLA; A K TRIVEDI; S SINGH; D N Giri (The Indian Journal of Agricultural Sciences, 2020)
Nine cultivars of bael (Aegle marmelos Correa.) were evaluated under subtropical conditions at Experimental Research Farm of ICAR-Central Institute for Subtropical Horticulture, Rehmankhera, Lucknow, in Randomized Block Design for two consecutive years, i.e. 2016 and 2017. The maximum terminal leaf length (13.50 cm) and breadth (8.40 cm) were recorded in cv. CISH-B-2, lateral leaf length (10.38 cm) in CISH-B-2 and lateral leaf breadth (6.54 cm) in NB-5. The flowering period started from 15th May and continued till 29th June with peak flowering observed during the second and third week of June. Fruit weight ranged 0.746 kg to 1.80 kg, fruit circumference from 37.5 to 50.01 cm and fruit length from 9.10–17.20 cm. Similarly, seeds/fruit varied from 82–156, number of seed sacs per fruit 11–18, seed percentage 0.36–1.08%, shell weight 0.150–0.548 g, shell percentage 14.46–21.54%, shell thickness 1.6–3.4mm. Pulp percentage varied from 57.63–82.39%. Rich variability was recorded in some biochemical traits of the fruits. The study exemplifes that ample variability is available in bael cultivars which may be utilized for improving production and productivity.